Bacterial Hsp90 Facilitates the Degradation of Aggregation-Prone Hsp70–Hsp40 Substrates - Fauvet, Bruno; Finka, Andrija; Castanié-Cornet, Marie-Pierre; Cirinesi, Anne-Marie; Genevaux, Pierre; Quadroni, Manfredo; Goloubinoff, Pierre (Frontiers in Molecular Biosciences, 2021)
In eukaryotes the Hsp90s are profusely-studied chaperones that, together with Hsp70s, control protein homeostasis. In bacteria however, the function of Hsp90 (HtpG) and its collaboration with Hsp70 (DnaK) remains poorly characterized. To uncover physiological processes that depend on HtpG and DnaK, we performed comparative quantitative proteomic analyses of insoluble and total protein fractions from unstressed wild type E. coli, and from knockout mutants ΔdnaKdnaJ (ΔKJ), ΔhtpG (ΔG) and ΔdnaKdnaJΔhtpG (ΔKJG) . Whereas the ΔG mutant showed no detectable proteomic differences with wild-type, ΔKJ expressed more chaperones, proteases and ribosomes and expressed dramatically less metabolic and respiratory enzymes. Unexpectedly, we found that ΔKJG showed higher levels of metabolic and respiratory enzymes than ΔKJ, suggesting that bacterial Hsp90 mediates the degradation of aggregation-prone Hsp70-Hsp40 substrates. Further in vivo experiments suggest that such Hsp90-mediated degradation possibly occurs through the HslUV protease.